The development of audio-visual media with contextual teaching learning approach to improve learning motivation and critical thinking skills - Khairani Sarwinda; Eli Rohaeti; Mirra Fatharani (Psychology, Evaluation, and Technology in Educational Research, 2020)
The study aims at developing the valid Contextual Teaching-Learning (CTL) Approach-based audio visual learning media in order to improve the learning motivation and the critical thinking skills significantly and also at identifying the effectiveness level of the Contextual Teaching-Learning (CTL) Approach-based audio visual learning media in improving the students’ learning motivation and critical thinking skills. Therefore, autoatically the nature of the study is research and development. During the conduct of the study, the data were gathered by using the random sampling technique. Then, the data gathering instruments that had been implemented were the media assessment questionnaire, the observation, the motivation questionnaire and the critical thinking skills test. The results of the study show that the Contextual Teaching-Learning (CTL) Approach-based audio-visual learning media that has been developed by using the Borg & Gall model is considered valid. The students’ learning motivation has increased as having been confirmed by the fact that the students are more enthusiastic, more interested and happier in attending to the learning process. Furthermore, the results of the students’ critical thinking skills test in the experimental group show that 25 students have met the passing grade while the remaining 6 students have not met the passing grade. On the other hand, the results of the students’ critical thinking skills test in the control group show that 20 students have met the passing grade while the remaining 12 students have not met the passing grade. In other words, these findings show that the learning process through the use of the Contextual Teaching-Learning (CTL) Approach-based audio-visual learning media is able to improve the students’ learning motivation and critical thinking skills.